STRATEGI ORANG TUA DALAM MENGEMBANGKAN REGULASI DIRI ANAK DENGAN ADHD ANAK DENGAN DISABILITAS INTELEKTUAL: Parental Strategies for Developing Self-Regulation in Children with ADHD and Intellectual Disabilities - Santa Maria Br Saragih Garingging; Sri Nurhayati Selian (Yayasan Al-Amin Qalbu, 2026)
Self-regulation is the fundamental skills that you need in your day-to-day life to control your emotions and behavior as well focused your attention on work. For some ADHD children, especially those with associated learning disabilities, self-regulation can present an even greater challenge, requiring parents most optimal involvement. The objective of the study was to explore parental strategies regarding the development of self-regulation in children with an empirical diagnosis of ADHD and intellectual disabilities (ID) by means of a literature review approach. this research method is a qualitative literature review by analysis: deliberately scrutinizing scientific sources. Parenting strategies that increase children`s self-regulation skills as clear parenting practices, daily routine, positive reinforcement with rats and when parents use emotional coaching (attention) to kids and parent modeling of their willingness to self-regulate such behaviours. Moreover, enhancing factors such as parental awareness, family support, school coordination and professional help reinforce the effectiveness of these strategies. Parenting stress, lack of knowledge, low financial status and social stigma are the major challenges that may slow down the developmental process. In conclusion, at least for children diagnosed with attention-deficit/hyperactivity disorder and intellectual disabilities, a concert between family, school and social environment is needed to maximize children cognitive-emotional-social development toward self-regulation